2011
DOI: 10.1002/glia.21122
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β negatively regulates oligodendrocyte differentiation and myelination in vivo

Abstract: Glycogen synthase kinase 3β (GSK3β) is an essential integrating molecule for multiple proliferation and differentiation signals that regulate cell fate. Here, we have examined the effects of inhibiting GSK3β on the development of oligodendrocytes (OLs) from their oligodendrocyte precursors (OP) in vivo by injection into the lateral ventricle of postnatal mice and ex vivo in organotypic cultures of isolated intact rodent optic nerve. Our results show that a range of GSK3β inhibitors (ARA-014418, lithium, indiru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
186
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(202 citation statements)
references
References 41 publications
13
186
1
2
Order By: Relevance
“…GSK3-b inhibition by lithium and other compounds promotes differentiation of oligodendrocytes from their precursors, myelination, and remyelination of lesions in the brain (Azim and Butt, 2011), as well as, in other districts, recovery of spinal lesions (Dill et al, 2008) and differentiation and myelination of Schwann cells (Ogata et al, 2004). Consistent data showed that GSK3-b is critical for establishing neuronal polarity, promoting neurite outgrowth, and turning mature neurites into axons in CNS neurons (Yoshimura et al, 2005).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…GSK3-b inhibition by lithium and other compounds promotes differentiation of oligodendrocytes from their precursors, myelination, and remyelination of lesions in the brain (Azim and Butt, 2011), as well as, in other districts, recovery of spinal lesions (Dill et al, 2008) and differentiation and myelination of Schwann cells (Ogata et al, 2004). Consistent data showed that GSK3-b is critical for establishing neuronal polarity, promoting neurite outgrowth, and turning mature neurites into axons in CNS neurons (Yoshimura et al, 2005).…”
Section: Introductionmentioning
confidence: 86%
“…Concerning myelin, GSK3-b inhibition by lithium and other compounds promotes differentiation of oligodendrocytes from their precursors, myelination, and remyelination of lesions in the brain (Azim and Butt, 2011). This pivotal study showed that GSK3-b inhibition promotes the proliferation of oligodendrocytes precursors and their differentiation into mature oligodendrocytes both in vivo in the adult and in the developing brain and ex vivo in organotypic cultures of optic nerve, and confirmed that when GSK3-b is inhibited by lithium, these effects involve an interaction between the Wnt pathway and other mechanisms (Azim and Butt, 2011).…”
Section: Lithium and Gsk3-b Effects On White Matter F Benedetti Et Almentioning
confidence: 99%
“…Right: A heavily myelinated peri-plaque region with rare FoxO3-labeled nuclei (black arrowheads). (D) FoxO3-labeled nuclei in a preterm WM lesion (Supplemental Table 1A; case 1) and MS plaques (Supplemental Table 1B tors of GSK3β Ser9 phosphorylation (e.g., LiCl, 6BIO) (46), which may account for observations that these inhibitors promoted OPC maturation (31). Several findings supported that bHAf regulates FoxO3 to block preOL maturation.…”
Section: Foxo3 Expression Is Markedly Increased In Oligodendroglia Inmentioning
confidence: 93%
“…However, there were no observed changes in mTOR phosphorylation status in response to bHAf that would suggest a role in bHAf signaling (Supplemental Figure 6D). Prior observations suggested that AKT inactivation results in GSK3β activation and that GSK3β inhibition enhances OPC maturation (31). We thus hypothesized that if bHAf blocked OPC maturation via GSK3β activation, treatment with a GSK3β kinase inhibitor should promote OPC maturation.…”
Section: Tlr4mentioning
confidence: 94%
“…Despite previous studies demonstrating up-regulation of Wnt signaling components in MS/EAE lesions, a role for this pathway in the pathogenesis of neuroinflammatory diseases remains unclear, because its effect depends on the specific cell type in which the pathway is active. Activation in oligodendrocytes suppresses their differentiation and myelination, and may be detrimental for repair processes within the CNS (44,46); however, Wnt signaling in dendritic cells suppresses neuroinflammation and ameliorates EAE by diminishing Th1/ Th17 immune responses (47).…”
mentioning
confidence: 99%